2018
DOI: 10.1007/s10853-018-2281-9
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT-based identification of double porosity in fired clay ceramics

Abstract: Optimizing thermal and mechanical properties of clay block masonry requires detailed knowledge on the microstructure of fired clays. We here identify the macro-and microporosity stemming from the use of three different poreforming agents (expanded polystyrene, sawdust, and paper sludge) in different concentrations. Micro-CT measurements provided access to volume, shape, and orientation of macropores, and in combination with X-ray attenuation averaging and statistical analysis, also to voxel-specific microporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The results for mercury intrusion porosimetry and total porosity agree well with a former report of Kariem et al, who also investigated pore structures of clay samples with organic additives . Rörig-Dalgaard et al reported an open porosity of clay bricks of about 33% (water saturation), which is in accordance with the porosity of the pure clay in Table .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results for mercury intrusion porosimetry and total porosity agree well with a former report of Kariem et al, who also investigated pore structures of clay samples with organic additives . Rörig-Dalgaard et al reported an open porosity of clay bricks of about 33% (water saturation), which is in accordance with the porosity of the pure clay in Table .…”
Section: Resultssupporting
confidence: 90%
“…The porosity of the individual specimens was examined by mercury intrusion porosimetry, including pore diameters smaller than 150 μm, as presented in Table . Bigger pores are beyond the measurement range; hence, the remaining part of pores was calculated by relating the apparent densities from weighing specimens with reference to the density of the pure clay, a method described elsewhere . Calculated total porosities are also indicated in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, micropores of size below the resolution of the SEM-images with 0:192 lm pixel size may still prevail. This is suggested by an intravoxel microCT-image analysis which was experimentally validated by weighing tests and mercury intrusion porosimetry [52]. Correspondingly obtained porosity values are about 8% higher than those obtained from present SEM-EDX results of Fig.…”
Section: Sem-edx Image Analysissupporting
confidence: 66%
“…For a constant applied voltage of the X-ray tube, there is a linear relationship between the greyscale level and the material density [47]. By virtue of this relationship, X-ray tomography can be used to measure local density variations within the material given proper calibration [48][49][50]. However, due to the complex material structure of cement paste, purely analytical solution mapping the attenuation to physical density has not been achieved to date.…”
Section: Experimental Results and Assumptionsmentioning
confidence: 99%